2008
DOI: 10.1177/147323000803600205
|View full text |Cite
|
Sign up to set email alerts
|

Tamsulosin Treatment of Chronic Non-bacterial Prostatitis

Abstract: The efficacy of tamsulosin in the treatment of chronic non-bacterial prostatitis was evaluated in a randomized clinical observation of 105 male outpatients conducted for 90 days. Patients were randomly divided into five groups (n = 21 per group) according to prostatitis type IIIA or IIIB and therapy regimens (tamsulosin, levofloxacin, or tamsulosin plus levofloxacin combination therapy). National Institutes of Health Chronic Prostatitis Symptom Index scores, expressed prostatic massage test and urodynamic uret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 7 publications
2
23
0
2
Order By: Relevance
“…Similar results were obtained in a comparison of doxazosin, levofloxacin and a combination of both, with the multimodal arm failing to provide any additional benefit over monotherapy [84]. However, small (n ≤ 105) comparative trials evaluating combinations of tamsulosin plus levofloxacin [73] and doxazosin plus ciprofloxacin [74] have shown that combined therapies outperformed monotherapy approaches in terms of NIH-CPSI score improvements. Evaluations of three-or four-component combinations of antibiotic, a-blocker, phytotherapy and/or physiotherapy techniques provide data in favour for combined therapies [51,85,86]; however, the lack of a control arm in these studies is a notable caveat Specialist physiotherapy Three small (n = 19-31) pilot studies [87][88][89] have shown that a pelvic floor biofeedback re-educating programme significantly reduces symptom severity in patients with CP/CPPS.…”
Section: A-reductase Inhibitorssupporting
confidence: 64%
See 1 more Smart Citation
“…Similar results were obtained in a comparison of doxazosin, levofloxacin and a combination of both, with the multimodal arm failing to provide any additional benefit over monotherapy [84]. However, small (n ≤ 105) comparative trials evaluating combinations of tamsulosin plus levofloxacin [73] and doxazosin plus ciprofloxacin [74] have shown that combined therapies outperformed monotherapy approaches in terms of NIH-CPSI score improvements. Evaluations of three-or four-component combinations of antibiotic, a-blocker, phytotherapy and/or physiotherapy techniques provide data in favour for combined therapies [51,85,86]; however, the lack of a control arm in these studies is a notable caveat Specialist physiotherapy Three small (n = 19-31) pilot studies [87][88][89] have shown that a pelvic floor biofeedback re-educating programme significantly reduces symptom severity in patients with CP/CPPS.…”
Section: A-reductase Inhibitorssupporting
confidence: 64%
“…More promising results were observed in a comparison of tetracycline hydrochloride vs placebo, with significant differences in NIH-CPSI scores and bacterial eradication rates; however, patient numbers were small (n = 48) [72]. Recent direct meta-analyses of these trials showed that antibiotics provide symptom improvement, but not at a significant level [63,64] Evidence from small (n = 20-105), randomised, comparative trials provides mixed support for using antibiotics in CP/CPPS, with significant differences from baseline in symptoms observed using levofloxacin [73], but not ciprofloxacin [74]; however, the ciprofloxacin study imposed a stringent significance threshold (P < 0.001)…”
Section: A-adrenergic Antagonistsmentioning
confidence: 99%
“…These treatments were ␣-blockers in 7 studies, 9,10,24,[33][34][35]38 antibiotics in 2 studies, 39,44 finasteride in 2 studies, 37,40 anti-inflammatory drugs in 4 studies, 11,12,22,43 phytotherapy in 3 studies, [13][14][15] glycosaminoglycan in 1 study, 41 and pregabalin in 1 study. 45 Three studies 21,36,42 had more than 2 treatment groups as follows: ␣-blockers plus antibiotics, ␣-blockers alone, and antibiotics alone in 2 studies 36,42 ; and ␣-blockers plus antibiotics, ␣-blockers alone, antibiotics alone, and placebo in 1 study. 21 Treatment duration ranged from 4 to 52 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…[38][52] Three of these trials compared antibiotics to alpha-blockers [18], [39], [48]. Five studies compared antibiotics to a combination of alpha-blockers and antibiotics [18], [39], [40], [48], [49]…”
Section: Resultsmentioning
confidence: 99%
“…All studies analyzed included descriptions of the statistical methods used and the inclusion and exclusion criteria for study participants (Table S3). Eight of the trials were sponsored by industry,[19][21], [26][28], [30], [32] six were clearly not sponsored by industry,[18], [22], [29], [33], [36], [48] and for the remaining 21 it was unclear in the text (Table S4)[23][25], [31], [34], [35], [37]–[47], [49][52].…”
Section: Resultsmentioning
confidence: 99%